Are Corpses the Best Method for Practical Anatomy Assessment, According to Health Course Students? - Soares, B. O.; Ribeiro, F. S.; Santos, I. F.; Silva, A. C. A. A.; Amorim, M.; Shiosaki, R. K.; Bettencourt Pires, M. A.; Schwingel, P. A.; Silva Júnior, E. X. (Journal of Morphological Sciences, 2018)
The aim of this study was to evaluate the student's conception in reference to the teaching materials used for the practical assessment of the discipline of Human Anatomy. The study was quantitative and qualitative, exploratory and descriptive. The materials were industrialized synthetic anatomical models, models made of inexpensive material by students, human cadaveric material, photocopied images and software. The study included 97 students, who after analysis indicated cadaveric materials (35%) as the best educational tool to be applied for the practical assessments of Anatomy. The photocopied images (3%) were the material with which the students presented greater difficulty. The content analysis of the discursive questions showed 5 factors in learning Human Anatomy: little time per table; difficulty in identifying, locating and memorization of anatomical structures; the quality of material used; comparing these materials; and cadaveric material. The study proved to be relevant for the evolution of teaching quality, in addition to the cadaveric material as the best tool to be used in practical assessments of Human Anatomy. We suggest the use of this material the more frequent, in laboratories that have the same materials as analyzed here, because the corpse can never be substituted in teaching and learning of Anatomy.
Keywords: gross anatomy education; software; photocopied images; anatomical structures manufacture; corpses prossected.